Bilateral Karapandzic flap: a work horse for carcinoma of lower lip - Narayana, Mada Lakshmi; D., Pramod; T., Lavanya; Viswambharan, Vivek; Gaur, Urvashi (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
The lips are major aesthetic components of the face, which are also necessary for facial expression, speech, and eating. In oncological resections, the main goal in lip reconstruction is achieving oral competence than speech and facial expressions. Malignant lesions involving lip warrant a wide excision to ensure a disease-free margin, which usually results in large defects. Defects up to 1/3rd of lips are closed primarily. Defects measuring 1/3rd to 2/3rd of the lower lip may be closed with Karapandzic, Abbe or Estlander flaps. A 45-year-old male presented with an exophytic lesion in the lower lip involving the facial skin with bilateral level 1b cervical lymphadenopathy. Contrast-enhanced computed tomography scan showed heterogeneous irregular lesion over the lower lip with bilateral enlarged necrotic level 1b cervical lymphadenopathy. Biopsy from the lesion was suggestive of moderately differentiated squamous cell carcinoma. Wide local excision with left modified radical neck dissection and right supraomohyoid neck dissection was done. The central lower lip defect was reconstructed with bilateral Karapandzic flap. The postoperative period was uneventful, although the patient had microstomia. The patient was advised adjuvant radiotherapy based on histopathology and was in regular follow up.